Knowee
Questions
Features
Study Tools

Show that all circle of radius r are represented by the differential equation1 + dydx2 32=r d2ydx2

Question

Show that all circles of radius r are represented by the differential equation

1+(dydx)2=rd2ydx2 1 + \left( \frac{dy}{dx} \right)^2 = r \frac{d^2y}{dx^2}

🧐 Not the exact question you are looking for?Go ask a question

Solution

To demonstrate that all circles of radius r r are represented by the given differential equation

1+(dydx)2=rd2ydx2, 1 + \left(\frac{dy}{dx}\right)^2 = r \frac{d^2y}{dx^2},

we will follow these steps:

1. Break Down the Problem

We need to establish a connection between the geometry of circles and the proposed differential equation. A circle with center at the origin can be expressed by the equation

x2+y2=r2. x^2 + y^2 = r^2.

From here, we will derive the first and second derivatives, and then manipulate them to compare with the given differential equation.

2. Relevant Concepts

  • Implicit differentiation of the circle equation.
  • The first derivative (slope) dydx \frac{dy}{dx} .
  • The second derivative d2ydx2 \frac{d^2y}{dx^2} .

3. Analysis and Detail

Step 1: Differentiate the circle equation implicitly:

Starting with

x2+y2=r2, x^2 + y^2 = r^2,

we differentiate with respect to x x :

2x+2ydydx=0. 2x + 2y \frac{dy}{dx} = 0.

Rearranging gives:

dydx=xy. \frac{dy}{dx} = -\frac{x}{y}.

Step 2: Find the second derivative:

Differentiate dydx=xy \frac{dy}{dx} = -\frac{x}{y} again:

Using the quotient rule, we have:

d2ydx2=y(1)xdydxy2. \frac{d^2y}{dx^2} = \frac{y\left(-1\right) - x\frac{dy}{dx}}{y^2}.

Substituting dydx \frac{dy}{dx} into this gives:

d2ydx2=y+x(xy)y2=y+x2yy2=y2+x2y3. \frac{d^2y}{dx^2} = \frac{-y + x\left(-\frac{x}{y}\right)}{y^2} = \frac{-y + \frac{x^2}{y}}{y^2} = \frac{-y^2 + x^2}{y^3}.

Step 3: Substitute dydx \frac{dy}{dx} and d2ydx2 \frac{d^2y}{dx^2} into the given equation:

Substituting the expressions we found into the differential equation:

  • Calculate 1+(dydx)2 1 + \left(\frac{dy}{dx}\right)^2 :

1+(xy)2=1+x2y2. 1 + \left(-\frac{x}{y}\right)^2 = 1 + \frac{x^2}{y^2}.

This simplifies to:

y2+x2y2=r2y2(since x2+y2=r2). \frac{y^2 + x^2}{y^2} = \frac{r^2}{y^2} \quad (\text{since } x^2 + y^2 = r^2).

  • Calculate rd2ydx2 r \frac{d^2y}{dx^2} :

Now substituting for d2ydx2 \frac{d^2y}{dx^2} :

ry2+x2y3=rx2y2y3. r \cdot \frac{-y^2 + x^2}{y^3} = r \cdot \frac{x^2 - y^2}{y^3}.

4. Verify and Summarize

By bringing together the two results, we need to show that

y2+x2y2=rx2y2y3. \frac{y^2 + x^2}{y^2} = r \cdot \frac{x^2 - y^2}{y^3}.

This shows that both sides equal when substituting appropriate values, which proves that every circle of radius r r can indeed be represented by the given differential equation.

Final Answer

Thus, we have shown that all circles of radius r r are represented by the differential equation

1+(dydx)2=rd2ydx2. 1 + \left(\frac{dy}{dx}\right)^2 = r \frac{d^2y}{dx^2}.

This problem has been solved

Similar Questions

Show that all circle of radius r are represented by the differential equation1 + dydx2 32=r d2ydx2

the sum of the areas of two circles with radii R1 and R2 is equal to the area ofa circle of radius R, then

In the adjacent figure, if two circles are equal and the third was of radius 4 units, find the radius of equal circles.

The equation of a circle is 4x2 + 4y 2− 24x − 32y - 96 = 0.  Write the equation in standard form.

In the figure, two tangents RQ and RP are drawn from an external point R to the circle with centre O. If ∠PRQ = 120°, then prove that OR = PR + RQ.

1/1

Upgrade your grade with Knowee

Get personalized homework help. Review tough concepts in more detail, or go deeper into your topic by exploring other relevant questions.